1999
DOI: 10.1046/j.1523-1755.1999.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss in long-term renal transplantation: Histopathology and densitometry analysis

Abstract: Long-term renal transplant-patients showed reduced BMD in both trabecular and cortical bone. This reduction in BMD was not as severe as in short-term reports and was associated with osteoclast stimulation, osteoblast suppression, and retardation of mineral apposition and bone formation rates. Bone mass loss was not different between the immunosuppression therapy groups. Male gender and age were the strongest predictive factors for low bone mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 31 publications
7
76
3
2
Order By: Relevance
“…These lesions were more severe in patients with less time after transplantation but approached normal values in patients who were Ͼ10 yr after transplantation. Similar results were shown by CuetoManzano et al (21) in the majority of patients. More recently, Monier-Faugere et al (18) in a study of posttransplantation patients after 4 to 6 yr showed bone alterations that were characterized by low bone turnover, decreased bone formation, and prolonged mineralization, whereas increased erosion surface was observed in fewer than 25% of the patients.…”
Section: Alterations Of Bone Remodeling After Transplantationsupporting
confidence: 91%
See 2 more Smart Citations
“…These lesions were more severe in patients with less time after transplantation but approached normal values in patients who were Ͼ10 yr after transplantation. Similar results were shown by CuetoManzano et al (21) in the majority of patients. More recently, Monier-Faugere et al (18) in a study of posttransplantation patients after 4 to 6 yr showed bone alterations that were characterized by low bone turnover, decreased bone formation, and prolonged mineralization, whereas increased erosion surface was observed in fewer than 25% of the patients.…”
Section: Alterations Of Bone Remodeling After Transplantationsupporting
confidence: 91%
“…Whereas Velasquez-Forero et al (19) showed mainly alterations that were consistent with adynamic bone disease and increased deposition of iron in the mineralization front, other studies have shown decreased bone formation and prolonged mineralization lag time in the presence of persisting bone resorption (4,20,21). Our studies in patients with normal renal function, after a mean of 7.5 yr after renal transplantation, showed mainly a mixed histologic pattern that was characterized by an increase in bone resorption, whereas bone formation rate was low and mineralization lag time prolonged (4).…”
Section: Alterations Of Bone Remodeling After Transplantationmentioning
confidence: 97%
See 1 more Smart Citation
“…Few studies have described the histology of the bone changes occurring after RT (3)(4)(5)(6). Most investigators have employed bone densitometry in the evaluation of post-transplant bone disease, but it is well known that bone biopsy provides the only reliable information about bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were not able to determine the various patterns of renal osteodystrophy (high or low bone turnover) because they were based on BMD findings. Currently, renal osteodystrophy is differentiated solely by means of a bone biopsy and histomorphometric analysis (2) and few prospective studies have evaluated this parameter (3)(4)(5)(6). For example, mild to moderate hyperparathyroidism is spontaneously reversed during the first 1 or 2 years after a successful RT (3).…”
Section: Introductionmentioning
confidence: 99%